The Effect of Financial Ratios On Fraudulent Financial Reporting - Vita Citra Mulyandini (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to examine the effect of Financial Ratios on Financial Statement Fraud in Manufacturing Companies Listed on the IDX for the 2014-2019 period. The population of this study were 15 companies. The sampling method used was purposive sampling method in order to obtain 15 companies as research samples. The data analysis technique used is Logistic Regression, Coefficient of Determination and Descriptive Analysis and Hypothesis Testing using the Wald Test and the Omnibus Test of Model Coeficients with a level of significance of 95%. The results partially show that profitability has a significant positive effect on Financial Statement Fraud, and Liquidity has a significant negative effect on Financial Statement Fraud. Meanwhile, it simultaneously shows that Profitability and Liquidity have a significant positive effect on Financial Statement Fraud in Manufacture Companies Listed on the Indonesia Stock Exchange (IDX) for the 2014-2019 Period.